THE INFLUENCE OF APPLICATION OF KOPIN MEDIA (SMART BOX) ON LEARNING OUTCOMES IN SCIENCE LEARNING CLASS V SDN 34 PALEMBANG - Sahara, Ms. Ai Ratna; Misdalina, Ms. Misdalina; Puspita Sari Jaya, Ms. Melinda (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The purpose of this study was to determine the effect of the application of KOPIN (Smart Box) Media on Learning Outcomes in Science Learning Class V SDN 34 Palembang. This research is a type of quantitative research using Quasi Experimental Design. This study used the Posttest Only Control Design research design. The variables of this study consisted of independent variables (X), namely the application of KOPIN (Smart Box) media and the dependent variable (Y), namely student learning outcomes. The population of this study were students of grades VA and VB SD Negeri 34 Palembang totaling 60 students, the samples taken were class VA as an experimental class of 30 students taught using KOPIN (Smart Box) media and class VB as a control class of 30 students taught using conventional learning models. In sampling using saturated sampling. The data collection techniques used in this study were tests and documentation. Data analysis techniques using normality test, homogeneity test and hypothesis testing. The calculated results show the value of tcount > ttable 5.203> 1.672 with degrees of freedom 58 (df 58). It can be concluded that it is significant where H0 is rejected while Ha is accepted, this is due to stating that there is an effect of the application of KOPIN (Smart Box) media on learning outcomes in science class learning.